Journey to the center of the earth - Miller, George; Collins, Connie; Hallmark Entertainment ([U.S] : Hallmark Entertainment ; Kuala Lumpur : Polinta Film Corporation [distributor])
Dr. Theodore Lytton (Treat Williams) heads an expedition to find the missing husband of Alice Hastings. Joined by his nephew and the trailblazing guide McNiff, the team descends into the sweltering, unknown depths of the earth
Title from title screen
Based on the novel by Jules Verne
Executive producer, Robert Halmi, Jr. David V. Picker ; teleplay by Thomas Baum
Casts: Treat Williams, Jeremy London, Bryan Brown
Keywords: Adventure films; Voyages to the otherworld -- Drama; Feature films